2008
DOI: 10.1016/j.trstmh.2008.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of repeated hand washing, sunlight, smoke and dirt on the persistence of deltamethrin on insecticide-treated nets

Abstract: Field studies were carried out in Iran to evaluate the effect of various factors (washing, sun, smoke, dust and dirt) on the residual insecticidal activity of PermaNet (a brand of long-lasting insecticidal net), and on nets conventionally treated with deltamethrin (K-O Tab), using bioassay tests. Thirty-two nets were washed five or 15 times, and eight nets were not washed at all. Nets were washed vigorously in cold tap water (17 degrees C, pH 8.9) with a detergent. Hand rubbing continued for 3min. After washin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 13 publications
5
19
1
1
Order By: Relevance
“…Moreover, as aphids are known to be major vectors of plant viruses (Ng andPerry 2004, Katis et al 2007), a repellent net suppressing contact between the vector and host plant should reduce signiÞcantly the impact of viral diseases in vegetable crop production. Nevertheless, nontoxic and sustainable alternatives to pyrethroids should be pursued for at least two reasons: 1) the observed pyrethroid resistance in M. persicae (Devonshire 1989, Field et al 1997, Field and Foster 2002 and in most vegetable sucking pests, such as Bemisia tabaci (Hemiptera: Aleyrodidae), another plant virus vector (Alon et al 2006, Houndete et al 2010; and 2) the risk of pesticide residues in rainwater-soaked plants and in soil, despite the use of a long-lasting treated net (Msangi et al 2008, Kayedi et al 2008, Dev et al 2010. Because the repellent AgroNet is easy to use on small vegetable plots, protecting them against lepidopterans, aphids, and other pests such as whiteßies and thrips, they could be an eco-friendly alternative to insecticide spray, particularly for small-scale farmers in tropical countries to protect their vegetables in urban and peri-urban areas (Ahouangninou et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as aphids are known to be major vectors of plant viruses (Ng andPerry 2004, Katis et al 2007), a repellent net suppressing contact between the vector and host plant should reduce signiÞcantly the impact of viral diseases in vegetable crop production. Nevertheless, nontoxic and sustainable alternatives to pyrethroids should be pursued for at least two reasons: 1) the observed pyrethroid resistance in M. persicae (Devonshire 1989, Field et al 1997, Field and Foster 2002 and in most vegetable sucking pests, such as Bemisia tabaci (Hemiptera: Aleyrodidae), another plant virus vector (Alon et al 2006, Houndete et al 2010; and 2) the risk of pesticide residues in rainwater-soaked plants and in soil, despite the use of a long-lasting treated net (Msangi et al 2008, Kayedi et al 2008, Dev et al 2010. Because the repellent AgroNet is easy to use on small vegetable plots, protecting them against lepidopterans, aphids, and other pests such as whiteßies and thrips, they could be an eco-friendly alternative to insecticide spray, particularly for small-scale farmers in tropical countries to protect their vegetables in urban and peri-urban areas (Ahouangninou et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To impregnate the bed nets with deltamethrin, a K-O tablet was dissolved in 0.5 liter of water in a plastic dish, and then a net was thoroughly soaked in it. In doing so, the amount of effective substance (deltamethrin) absorbed by the fiber of each net was 25 mg /m 2 19 .…”
Section: Methodsmentioning
confidence: 99%
“…The hard spring water was also chlorinated before entering the water supply network. After each washing, half of the PermaNet ® 2.0 bed nets and half of the bed nets impregnated with K-O tabs were shade-dried for three hours, and the other half of nets were sun-dried for three hours 19 . The same procedure was followed for the control bed nets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas deltamethrin has lost its activity after than other insecticides [13]. It was concluded that the effect of sun is much smaller than that of washing, and drying nets for a few hours in the sun is not harmful [14]. Reported studies in 2008 shown that out of 11460 malaria cases of Iran, 8% was due to P. falciparum, while 90% were infected by P. vivax (Minsitry of Health 2008).…”
mentioning
confidence: 99%